Prevalence and Characteristics of Regular Hemodialysis Patients with COVID-19 at USU Hospital in 2020-2021 at the University Hospital of North Sumatra - M. Feldi Gazaly Nasution (Faculty of Medicine, Universitas Andalas, 2023)
Background: In 2019, the outbreak of the Coronavirus disease (COVID-19) due to infection with the Coronavirus 2 (SARS-CoV-2) spread rapidly to other countries. These patients are at higher risk of contracting COVID-19 infection. Method: The design of this study is a descriptive study with a retrospective cross-sectional study approach which aims to determine the prevalence and characteristics of Regular HD patients with Covid 19 at USU Hospital Medan. The research data was taken from the patient's medical record and then processed using the SPSS application. Result: URR examination had a significant difference between the two groups, where the living group had a higher value than the dead group. The living group had higher average levels of hemoglobin, platelets, and albumin, while the creatinine level was lower than the dead group. Conclusion: The URR value was high in the living group compared to the dead group. A high URR value describes better HD adequacy and is associated with an improvement in quality of life compared to a low URR value. The results showed that the levels of hemoglobin, platelets, albumin, CRP, and creatinine had significant differences. The creatinine level was lower than the dead group.